Lipoprotein (a) in the Development and Progression of Diabetic Retinopathy: A Systematic Review and Meta-Analysis - Stamatios Lampsas; Vaia Lambadiari; Chrysa Agapitou; Aikaterini Lampsa; Evangelos Oikonomou; Gerasimos Siasos; Irini Chatziralli (Medicina)
Background and Objectives: Diabetic retinopathy (DR) is a significant complication of Diabetes Mellitus. Several studies have indicated Lipoprotein (a) [Lp(a)] plays a role in atherosclerotic alterations. Materials and Methods: This meta-analysis/systematic review aims to investigate the connection between Lp(a) and DR. All relevant studies indexed in PubMed and Scopus from up to January 2025 were included. A total of 29 studies (7007 subjects) were included, and the results were synthesized according to the PRISMA Guidelines. The results are presented as standardized mean differences (SMDs) with 95% confidence intervals (CIs) derived using random effects models. Results: The mean age of the included subjects was 52.6 ± 9.4 years, with 52.5% being male. The primary analysis included 25 observational studies involving a total of 6291 subjects (2770 patients with DR vs. 3521 controls). Notably, Lp(a) levels were significantly higher in patients with DR compared to those in controls, with an SMD of 0.85 (95% CI: 0.48–1.22; p < 0.001, I2 = 98%). Interestingly, a secondary analysis of the patients with Proliferative Diabetic Retinopathy (PDR) and Non-Proliferative Diabetic Retinopathy (NPDR) yielded an SMD of 0.28 (95% CI: 0.09–0.47; p = 0.004, I2 = 97%) between the two compared groups. In this analysis, a total of 1066 patients (465 PDR patients vs. 601 NPDR patients) were included. Conclusions: Elevated Lp(a) levels may have a compelling relationship with the development and progression of DR based on the evidence analyzed.